Development of Physics Teaching Module for Phase-E with the CDT (Component Display Theory) Approach - Pujijana Purnawati; Masri Kudrat Umar; Tirtawaty Abdjul (Postgraduate, University of Mataram, 2023)
This research aims to develop a physics teaching module for phase-E with a CDT approach and to obtain the product's feasibility by meeting the validity, practicality, and effectiveness indicators. The research type is developmental research with a 4D model. This research was carried out at SMA Negeri 1 Wonosari. The average validation scores for the teaching module components were 3.4, indicating that the module is valid and suitable for use. Teacher observation scores for both limited and extensive testing were 96.7% and 88.3%, respectively, while student response questionnaire scores were 83.16% and 85.28%. Both instruments indicated that the teaching module is practical and suitable for use. The average student engagement observation scores for limited and extensive testing were 85.3% and 84.6%, and the average test scores for learning outcomes in both tests were 84.95%. These results suggest that the teaching module is effective and has a positive impact on improving student learning outcomes. Therefore, the development research on the physics teaching module for phase-E with a CDT approach is valid, practical, and effective.